Da intolerância à tolerância: um olhar semiótico à campanha publicitária - Nem Uma Vez - Biavatti, Paola (2024)
This study focuses on the enunciative-discursive mechanisms used in an advertising campaign about human rights in favor of tolerance. The aforementioned campaign, entitled ¿Also forming better human beings: some attitudes are not tolerable #NemUmaVez¿, was designed in order to promote the awareness of aggressors and victims about situations of prejudice experienced on the campus of the Faculty of Medicine of Ribeirão Preto, of the University from São Paulo. In this sense, our general objective is to explain the enunciative-discursive strategies mobilized in the advertising campaign “Also forming better human beings: some attitudes are not tolerable #NemUmaVez”, identifying mechanisms that promote reader adherence to the discourse conveyed. To do this, we focus on studies on the construction of identity, otherness, dialogism and the construction of intolerant discourses based on Landowski (2012, 2023), Bakhtin (2002, 2011) and Barros (2005a, 2011, 2014, 2016), in the main concepts of discursive semiotics, such as content plan and its generative path of meaning, expression plan and its categories of analysis, and enunciative strategies and their meaning effects, based on Greimas and Courtés (1973, 1990, 2021), Fiorin ( 1998, 2012a, 2012b, 2021, 2022a, 2022b), Barros (2001, 2005b), Pietroforte (2004) and Teixeira (2001, 2008, 2009), and on the notions of discursive genre, social advertising and persuasion, based on Bakhtin (2011), Fiorin (1988), Torres e Leite (2017) and Balonas (2006). The research corpus is made up of four advertising pieces from the campaign, which allude to racism, violence against women, homophobia and aporophobia. The research, of a basic nature, is established as explanatory from the point of view of its objectives, bibliographic regarding its technical procedures, and qualitative in the type of approach used. The established methodological path proposes the analysis of categories of the content plan, the expression plan, the articulation strategies of these plans in the textual arrangement and the meanings they produce, also taking into account interdiscourses with which the advertising pieces dialogue. The results obtained in the analysis demonstrate that the arrangements of the plane of expression, with the colors, shapes and arrangement of the figures in space, placing the oppressor on a plane in front of the oppressed, and the main statements of each piece, which evoke interdiscourses about the groups figurativized in the campaign and using the first person (I) to create effects of a sense of proximity and subjectivity, they contribute to making the piece impactful and promoting reader adherence to the discourse conveyed.